An interactive approach to determine optimal launch time of successive generational product. (1st January 2014) - Anand, Adarsh; Singh, Ompal; Aggrawal, Deepti; Singh, Jagvinder
Effective product launch and commercialisation are critical drivers of top performance for the firms; to which a strong product launch greatly improves the chances of success. Launch is often the single costliest step in new product development. Despite its importance, costs, and risks, product launch has been relatively under researched in the product literature. Determination of optimal launch time is especially critical for high-technology products, where the introduction of each successive generation of a product requires the firm to explicitly consider its impact on the demand for preceding generations. The timing of the launch (i.e., when the launch is conducted from the point of view of the company, the competition, and the customer) is just as important as whether the activities are performed. More managerial attention should be devoted to launch timing with respect to all of these viewpoints in order to improve the chances of success. This study identifies attributes such as speedy launch and cost that affect the introduction time of new generation. To trade-off between two decision factors, multi-attribute utility theory (MAUT) is applied in our innovation diffusion process incorporated decision model. The optimisation model is supplemented with numerical illustration done on a real life dataset.